Family Health Outcomes during Economic Crises: the Role of Household Nutrition Coping Strategies - I Nyoman Adiyasa; Aliah Bagus Purwakania Hasan (Global Medical & Health Communication (GMHC), 2026)
The prolonged economic downturn at both national and household levels has significantly disrupted food access, altered dietary patterns, and increased the risk of nutrition-related health problems. This study aimed to identify household nutrition coping strategies during economic hardship and examine their association with family health outcomes, particularly among vulnerable groups such as women and young children. A cross-sectional survey was conducted from February to April 2025 involving 210 households in Denpasar (Bali) and Mataram (West Nusa Tenggara). A purposive sampling technique was applied to select households experiencing income decline and changes in food consumption. Data were collected using a structured questionnaire assessing food security status, dietary patterns, and coping behaviors, complemented by basic health indicators. Data were analyzed using descriptive statistics, chi-square tests, and Spearman correlation analysis. The results indicate that 68% of households reduced meal portions, 63% substituted nutritious foods with cheaper alternatives, and 47% reduced meal frequency. A significant association was found between coping strategy categories and household health symptoms (p<0.05). Furthermore, a moderate positive correlation was observed between coping intensity and family health symptom scores (r=0.482, p<0.01), indicating that households employing more coping strategies tended to report higher levels of health-related complaints. Approximately 36% of households reported weight loss among children, and 29% reported decreased appetite. These findings suggest that while coping strategies serve as short-term adaptive mechanisms, their frequent use is associated with declining dietary quality and increased health vulnerability among family members. Strengthening community-based nutrition resilience programs and integrating responsive social protection policies are essential to mitigate the long-term health impacts of economic crises. This study provides empirical evidence on the relationship between coping behavior and household health outcomes in vulnerable urban and semi-urban populations.